Combinations of drugs in the Treatment of Obesity - Marcio C. Mancini; Maria Edna de Melo; Cintia Cercato; Alfredo Halpern; André M. Faria; Eduardo S. L. Oliveira; Bruno Halpern (MDPI AG, 2010)
Obesity is a chronic disease associated with excess morbidity and mortality. Clinical treatment, however, currently offers disappointing results, with very high rates of weight loss failure or weight regain cycles, and only two drugs (orlistat and sibutramine) approved for long-term use. Drugs combinations can be an option for its treatment but, although widely used in clinical practice, very few data are available in literature for its validation. Our review focuses on the rationale for their use, with advantages and disadvantages; on combinations often used, with or without studies; and on new perspectives of combinations being studied mainly by the pharmaceutical industry.